ANALYSIS OF THE NEED FOR DIGITAL GAME-BASED LKPD TO IMPROVE PRIMARY SCHOOL STUDENTS' CRITICAL REASONING ABILITY - Citra Kumala Waty; Puji Sugiyartini (Universitas PGRI Semarang, 2023)
The purpose of this article is to determine the level of need for using game-based digital LKPD in improving critical reasoning skills. The method used is descriptive qualitative. Data collection techniques used questionnaires and interviews. The data analysis technique uses descriptive through interview activities and quantitative based on the percentage of questionnaire distribution results via Google Forms. The results of the initial needs analysis of students regarding the need for game-based digital LKPD are (53.5%) of students strongly agree in using Wordwall media, (46.5%) of students agree with using Wordwall media, (0%) students do not agree in using media Wordwall, (0%) of Students show a high level of disapproval of the use of Wordwall media. However, in thematic learning using Wordwall media, its effectiveness can be seen from the majority of students who strongly agree or agree, reaching 98.2%. This is compared to the minority of students who disagree or strongly disagree, which is only 1.8%. and it was found that 85.3% of students were able to complete the evaluation of KKM questions and 14.7% still needed to receive special guidance from educators. From the results of this analysis, the need for game-based digital LKPD is very effective in learning activities to improve elementary school students' critical reasoning abilities.